2018
DOI: 10.1371/journal.pone.0196797
|View full text |Cite
|
Sign up to set email alerts
|

A flavin-dependent halogenase from metagenomic analysis prefers bromination over chlorination

Abstract: Flavin-dependent halogenases catalyse halogenation of aromatic compounds. In most cases, this reaction proceeds with high regioselectivity and requires only the presence of FADH2, oxygen, and halide salts. Since marine habitats contain high concentrations of halides, organisms populating the oceans might be valuable sources of yet undiscovered halogenases. A new Hidden-Markov-Model (HMM) based on the PFAM tryptophan halogenase model was used for the analysis of marine metagenomes. Eleven metagenomes were scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(117 citation statements)
references
References 58 publications
(79 reference statements)
2
112
0
3
Order By: Relevance
“…BAL3, exhibits a high preference of indole bromination over chlorination. Conversely, Trp halogenases are reported to favor incorporation of less bulky chloride . Hence, we examined whether Thal mutagenesis also influences halide selectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BAL3, exhibits a high preference of indole bromination over chlorination. Conversely, Trp halogenases are reported to favor incorporation of less bulky chloride . Hence, we examined whether Thal mutagenesis also influences halide selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, Trp halogenases are reported to favor incorporation of less bulky chloride. [15,55] Hence, we examined whether Thal mutagenesis also influences halide selectivity. LC-MS analysis confirmed Thal-GWV's ability to incorporate either chloride or bromide into l-Trp with high efficiency.…”
Section: Further Characterization Of Evolved Variant Confirmed Maintamentioning
confidence: 99%
“…Investigations on novel halogenases or engineering the existing ones, for broader substrate scope, enhanced activity, and stability have been conducted. [18,[37][38][39][40][41] Xanthomonas comprises a group of Gram negative Proteobacteria infecting over 350 monocotyledonous and dicotyledonous plant species. [42] The plant pathogen Xanthomonas campestris (Xcc) is a member of this group infecting crucifers like cabbage and cauliflower.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, FDHs were identified that halogenate substituted tryptophan (12,13) or chlorinate tryptophan only when it is part of a substrate oligopeptide (14). FDHs acting on free substrates other than tryptophan were also described (15)(16)(17)(18), including fungal enzymes that accept large substrates (19 -21) or have rather broad substrate specificity (22,23), raising the hope that diverse compounds can be enzymatically halogenated in vitro. Moreover, FDHs have been integrated into engineered biosynthetic pathways in vivo (24,25).…”
mentioning
confidence: 99%